2016
DOI: 10.1002/anie.201510554
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Promiscuity of Transaminases: Preparation of Enantioenriched β‐Fluoroamines by Formal Tandem Hydrodefluorination/Deamination

Abstract: Transaminases are valuable enzymes for industrial biocatalysis that enable the preparation of optically pure amines. For these transformations they require either an amine donor (amination of ketones) or an amine acceptor (deamination of racemic amines).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…[10] Other examples using organocatalytic catalysts have been provided by Lindsley and co-workers, [11,12] who performed the enantioselective fluorination of N-sulfinyl aldimines, followed by nucleophilic addition using a Grignard reagent, providing the final compounds in high dr (> 20 : 1).More recently, we showed that amine transaminases (ATAs) can be applied to the 100 mg scale asymmetric synthesis of βfluoroamines, with up to 99 % ee., through the kinetic resolution of racemic substrates. [13] A series of racemic β-fluoro arylethylamines including 1 b and 2 b (Scheme 1) was converted by both (S)-and (R)-selective ATAs to give the corresponding enantiopure β-fluoroamines, in addition to acetophenones 3 a and 4 a, co-products that arise through the enantioselective tandem hydrodefluorination-deamination process that is catalyzed by the enzymes.However, the applicability of the method is compromised, owing to the maximum 50 % yields that may be achieved, and the concomitant inhibition of the ATAs used, due to the formation of a covalent adduct with PLP in the active site of the enzyme.A solution to the limited yield of the ATA-catalyzed process is presented by imine reductases (IREDs). [14,15] When presented with ketones, such as acetophenone, and a large excess of ammonia or other amine, these NADPH-dependent enzymes catalyze the asymmetric reduction of imines formed in solution, to give chiral amine products such as α-methylbenzylamine (3 b) in a theoretically quantitative yield and with high enantiomeric excess (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Other examples using organocatalytic catalysts have been provided by Lindsley and co-workers, [11,12] who performed the enantioselective fluorination of N-sulfinyl aldimines, followed by nucleophilic addition using a Grignard reagent, providing the final compounds in high dr (> 20 : 1).More recently, we showed that amine transaminases (ATAs) can be applied to the 100 mg scale asymmetric synthesis of βfluoroamines, with up to 99 % ee., through the kinetic resolution of racemic substrates. [13] A series of racemic β-fluoro arylethylamines including 1 b and 2 b (Scheme 1) was converted by both (S)-and (R)-selective ATAs to give the corresponding enantiopure β-fluoroamines, in addition to acetophenones 3 a and 4 a, co-products that arise through the enantioselective tandem hydrodefluorination-deamination process that is catalyzed by the enzymes.However, the applicability of the method is compromised, owing to the maximum 50 % yields that may be achieved, and the concomitant inhibition of the ATAs used, due to the formation of a covalent adduct with PLP in the active site of the enzyme.A solution to the limited yield of the ATA-catalyzed process is presented by imine reductases (IREDs). [14,15] When presented with ketones, such as acetophenone, and a large excess of ammonia or other amine, these NADPH-dependent enzymes catalyze the asymmetric reduction of imines formed in solution, to give chiral amine products such as α-methylbenzylamine (3 b) in a theoretically quantitative yield and with high enantiomeric excess (Scheme 2).…”
mentioning
confidence: 99%
“…More recently, we showed that amine transaminases (ATAs) can be applied to the 100 mg scale asymmetric synthesis of βfluoroamines, with up to 99 % ee., through the kinetic resolution of racemic substrates. [13] A series of racemic β-fluoro arylethylamines including 1 b and 2 b (Scheme 1) was converted by both (S)-and (R)-selective ATAs to give the corresponding enantiopure β-fluoroamines, in addition to acetophenones 3 a and 4 a, co-products that arise through the enantioselective tandem hydrodefluorination-deamination process that is catalyzed by the enzymes.However, the applicability of the method is compromised, owing to the maximum 50 % yields that may be achieved, and the concomitant inhibition of the ATAs used, due to the formation of a covalent adduct with PLP in the active site of the enzyme.…”
mentioning
confidence: 99%
“…[5] UCB pharma has developed several synthetic routes for the preparation of the 2-oxo-pyrrolidine derivative, [6][7][8] however, these exclusively chemical methods come along with poor stereoselectivity and hence elaborate chromatography steps in order to obtain the far more active (2S,4R)-stereoisomer in pure form. Interestingly, despite of their popularity for the synthesis of chiral amines used for APIs and their successful application also on industrial scale, [24][25][26][27][28][29][30][31] transaminases (TA) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] have not yet been considered as the biocatalyst of choice to prepare key intermediates of Pregabalin and Brivaracetam by deracemisation of the corresponding aldehydes. This process has been improved in terms of yield and economical aspects by replacing chemical resolution by a lipasecatalysed one.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Only ah andful of examples have been reported involving enantioselective transformations with modest enantiomeric excess. [16][17][18][19][20][21][22][23][24] These enzymes have also been combined in cascades to carry out multiple transformations in one pot, often with the oxidation and reduction steps taking place concurrently. [16][17][18][19][20][21][22][23][24] These enzymes have also been combined in cascades to carry out multiple transformations in one pot, often with the oxidation and reduction steps taking place concurrently.…”
mentioning
confidence: 99%
“…[13][14][15] Biocatalysis offers avariety of methods for the asymmetric synthesis of amines,i ncluding transaminases (TAs), monoamine oxidases (MAO-N), phenylalanine ammonia lyases (PALs), amine dehydrogenases (AmDHs), and imine reductases (IREDs). [16][17][18][19][20][21][22][23][24] These enzymes have also been combined in cascades to carry out multiple transformations in one pot, often with the oxidation and reduction steps taking place concurrently. [25][26][27] Recently,w er eported the discovery of anew enzyme,areductive aminase from Aspergillus oryzae (AspRedAm), [28] which catalyzes the reductive amination of av ariety of carbonyl compounds at low amine loadings with good to excellent stereoselectivity.T his discovery prompted us to consider the application of AspRedAm in the hydrogenborrowing amination of alcohols.…”
mentioning
confidence: 99%